The Delang Isolect: A Synchronic Description on Its Phonemic System, Retention, and Innovation - Ralph Hery Budhiono (Balai Bahasa Kalimantan Tengah, 2021)
Problem to be discussed in the research is how does the phonemic system of the Delang and its retention and innovation to be compared with its proto Austronesia (PAN). This research is aimed to identify the character of the Delang descriptively, out from its status either as an independent language or just a dialect or subdialect of a certain language. The research hopefully can give more knowledge contributions especially for the speaker and the community at large. This is a descriptive research with synchronic-qualitative approach. The data will be 200 basic lexicons from Swadesh that is compiled by the language mapping team of Balai Bahasa Kalimantan Tengah in 2019. The analysis is started from the description of the Delang phonemic system. The phonemic retention and innovation come from comparing the lexicons with its Blust ‘s PAN. Based on the analysis the writer underlined some conclusions. The isolect has 5 vowels and 18 consonants. Some protophonemes, like *a and *u in certain positions, are maintained, while some other phonemes are innovated or substituted. Some secondary innovations found, namely prothesis, syncope, metathesis, aphaeresis, and fortition.AbstrakPenelitian ini bertujuan untuk mengidentifikasi isolek Delang secara lebih mendalam, terlepas dari statusnya sebagai bahasa mandiri atau dialek dari bahasa lain. Penelitian ini diharapkan dapat memberikan pengetahuan kepada penutur isolek Delang khususnya dan masyarakat pada umumnya terkait dengan sistem, pemertahanan, dan inovasi fonemik dalam isolek itu. Metode yang digunakan dalam penelitian ini ialah deskriptif dengan pendekatan sinkronis-kualitatif. Data yang merupakan 200 kata dasar Swadesh dikumpulkan tahun 2019 oleh tim pemetaan Balai Bahasa Kalimantan Tengah dan berupa data mentah yang belum ditranskripsikan. Analisis dimulai dari deskripsi sistem fonemis isolek itu. Retensi dan inovasi fonemik didapatkan dari perbandingan antara 200 kosakata dasar isolek itu dan PAN versi Blust. Berdasarkan analisis diperoleh beberapa simpulan. Isolek Delang memiliki 5 vokal dan 18 konsonan. Beberapa fonem proto, seperti *a dan *u, pada posisi tertentu dipertahankan, sedangkan fonem lain diinovasikan atau diubah. Inovasi sekunder yang didapatkan ialah protesis, sinkope, metatesis, afaeresis, dan fortisi.